ULTRASONIC STUDIES ON SOME AQUEOUS SOLUTIONS OF CARBOHYDRATES AT THREE DIFFERENT TEMPERATURES (Biological Sciences - PJSIR, 2004)
Density, viscosity and ultrasonic velocity measurements have been performed by ultrasonic interferometer technique in some aqueous solutions of three carbohydrates (sucrose, D-glucose and b-D lactose) as a function of molality with different concentration of the order 0.1 to 0.5 mole/kg. At three different temperatures, via 303.15K, 313.15K and 323.15K and at atmospheric pressure, ultrasonic velocity, partial molar volumes, partial molar isentropic compressibility have been calculated and plotted against concentration. The velocity results confirm the conclusions that were originally deri- ved from viscosity data by Einstein that the sugar molecules have a ‘salvation envelope’ attached with a layer of water molecules which decreases with thickness as the temperature of the solution rises. It has been observed that in such solutions it is quite legimate to look for the dispersion caused by viscosity of the solutions. The apparent molar volume occupied by solute molecules remains constant at one particular temperature, irrespective of the change in concentration of sucrose in water. The compressibility increases slowly as a function of concentration at constant temperature. The data revealed that the compressibility of these different solutions is related with three diamensional hydrogen bond water structure. It is governed by the stereochemistry of carbohydrate. By these studies an overview of the hydration charac- teristics and the effect of relative position of hydroxyl group within a carbohydrate molecule is given. By increasing the carbohydrate concentration in water the ultrasonic velocity increases, while there is no effect on compressibility of moles. For monomer the apparent molal compressibility depends on the hydration of the mole. The results agree with the previ- ously obtained kinematics data of literature values.